Pengaruh Penerapan JIT (Just In Time) Dan TQM (Total Quality Management) Terhadap Delivery Performance Pada Industri Otomotif Di Indonesia - Brigita Meylianti S; Fernando Mulia (Universitas Airlangga, 2009)
This research discusses the impact of JIT (Just In Time) and TQM (Total Quality Management) application to Delivery Performance. Either JIT or TQM is two concept in management science specially operation management, but in fact that exist in Indonesian companies most of them have not yet applied these concept properly. Many of Indonesian companies applied latest management concept just to keep up with the trend. Unfortunately these concepts might have not been suitable if it applied directly for Indonesian circumstances. This research was conducted in automotive industry, this election is based on history that at the first JIT and TQM born in automotive industry so unquestionable the application of these concepts in this industry is better than other kind of industry. In other hand delivery performance is focus on excellent timing and excellent quality of product produced. Theoretically, JIT application is inseparable form TQM application or vice versa, it one of them applied without application if the other, the result will not be an optimum one. But it is important to remember that large number of existing theories nowadays, was develop in Europe, America and the nearest Japan. There is large number of differences, even the fundamental one in social and culture, it effect to thinking pattern, and working spirit. Indonesia has different culture to Europe, America and Japan. Frequently the application of JIT and also TQM are fail to give significant improvement to company’s performance. It issues some emerging questions: Do JIT and TQM have influence to performance specially delivery performance? Do JIT have influence to performance specially delivery performance? Do TQM have influence to performance specially delivery performance? This research will answer the emerging questions. Following data collection and data processing, the result conclusion will be: JIT and TQM have significant linear influence to delivery performance. In partial, JIT does not give significant linear influence to delivery performance, whereas TQM gives significant linear influence to delivery performance.